Coriander Aphid, Hyadaphis coriandri (Das) (Insecta: Hemiptera: Aphididae) - Susan E. Halbert (EDIS, 2005)
The coriander aphid, Hyadaphis coriandri (Das), was found for the first time in North America on fennel (Foeniculum vulgare Mill.) at Orange County residences in Apopka and Orlando. In December 1998, an infestation also was found on coriander (Coriandrum sativum Linnaeus) and dill (Anethum graveolens Linnaeus) at a residence in Tampa, Hillsborough County. This document is EENY-296 (originally published as DPI Entomology Circular 399), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2003.